ESP1 within ESP: the design and implementation of a pronunciation module in a technical English course - Quesada Vázquez, Leticia; Romero, Joaquín (Onomázein, 2020)
This paper focuses on the design and implementation of a ten-week pronunciation module within a university technical English course as part of a broader study that investigates the efficacy of explicit rhythm instruction to improve engineering students’ prosody in English. Sessions were adapted to the course contents and followed Celce-Murcia, Brinton & Goodwin's (1996) steps to teach communicatively. The participants were 298 Spanish/Catalan-speaking first-year undergraduate engineering students divided into three experimental groups and three control groups. The experimental groups received explicit rhythm instruction while the control groups did not. They all were recorded before and after the training. Ten sentences were analyzed acoustically and measures of rhythm (VarcoV) were obtained. Preliminary results revealed that students who took rhythm instruction tended to increase their VarcoV values, approaching English rhythm, while the control group showed a volatile behavior. The comparison of the effect sizes of each group’s differences in performance before and after instruction was statistically significant. Findings suggest that rhythm instruction can be beneficial to enhance EFL students’ prosody and that pronunciation can be effectively introduced within an ESP course.